MANAJEMEN HUMAS UNTUK MENINGKATKAN KREDIBILITAS SEKOLAH - Deddiliawan, Agung; Arafat, Yasir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
Public’s recognition is one of the method to increase the credibility of a school and by using this term, the school’s publication has become an urgent matter. The purpose of this community service is to give assistance to the public relation of SMK 9 Wagir (Vocational High School 3 Wagir) to elevate the school’s credibility by designing a website for the school to introduce the institution to the public. The method used in elevating the school’s credibility involves: (1) conducting workshop in public relation management, (2) conducting website management workshop, (3) doing website designing assistance, (4) evaluating the whole process. The product as a result expected from this community service is a ready to access website to introduce the institution to the public and journal article related to the matter.